2005
DOI: 10.1210/jc.2004-1429
|View full text |Cite
|
Sign up to set email alerts
|

Human Lymphocyte-Synthesized Melatonin Is Involved in the Regulation of the Interleukin-2/Interleukin-2 Receptor System

Abstract: Since melatonin was first isolated in 1958 up to the last few years, this substance was considered a hormone exclusive to the pineal gland. Although melatonin has lately been identified in a large number of extrapineal sites, its potential biological actions have not yet been studied. This paper shows that human lymphocyte-synthesized melatonin plays a crucial role modulating IL-2/IL-2 receptor system because when blocking melatonin biosynthesis by the tryptophan hydroxylase inhibitor, parachlorophenylalanine,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
100
0
11

Year Published

2005
2005
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 143 publications
(117 citation statements)
references
References 49 publications
6
100
0
11
Order By: Relevance
“…However, experimental evidence implicating the role of melatonin in regulation of diurnal variation in phagocytosis is lacking. In the present study, administration of pCPA, an irreversible tryptophan hydroxylase inhibitor known to diminish melatonin biosynthesis (Carrillo-Vico et al 2005), completely abolished the decrease in phagocytosis observed during dark phase. The decreased melatonin level might be implicated for this effect though the serum melatonin was not measured in these spotted murrel fish.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…However, experimental evidence implicating the role of melatonin in regulation of diurnal variation in phagocytosis is lacking. In the present study, administration of pCPA, an irreversible tryptophan hydroxylase inhibitor known to diminish melatonin biosynthesis (Carrillo-Vico et al 2005), completely abolished the decrease in phagocytosis observed during dark phase. The decreased melatonin level might be implicated for this effect though the serum melatonin was not measured in these spotted murrel fish.…”
Section: Discussionsupporting
confidence: 61%
“…pCPA is a known irreversible tryptophan hydroxylase inhibitor, and hence, diminishes the melatonin synthesis (Carrillo-Vico et al 2005). A single dose of pCPA (100 mg/kg body weight) in C. punctatus is reported to considerably reduce serotonin that is the precursor of melatonin, within 2 h of its administration.…”
Section: Role Of Pineal Hormone Melatonin In Diurnal Variation In Phamentioning
confidence: 99%
“…In rat microvasculature, MT 2 activation also reduces acute inflammation by inhibiting leukocyte rolling (Lotufo et al, 2001). In human lymphocytes MT 1 receptor activation counteracts the inhibitory effect of prostaglandin E 2 on interleukin 2 production (Carrillo-Vico et al, 2003;Carrillo-Vico et al, 2005). Activation of MT 2 receptors modulates immune responses, providing a mechanism by which endogenous melatonin may participate in adaptation to seasonal changes (Table 1).…”
Section: B Melatonin Receptor Functionmentioning
confidence: 99%
“…In particular, endogenous production of melatonin by human lymphocytes has been related to enhanced release of IL-2 and upregulation of IL-2R (20), suggesting that melatonin may be involved in the clonal expansion of Ag-stimulated human T lymphocytes. Importantly, the effects of melatonin on activated T cell death remain largely unknown.…”
mentioning
confidence: 99%